Neither male nor female: Poetic imagery and the nature of God in the Old Testament - McConville, James Gordon (Journal for the study of the Old Testament, 2019)
The article considers the relationship between the metaphorical language for God used in the poetry of the Old Testament, especially female metaphors, and the Old Testament's portrayal of the nature of God. It considers two opposing views: first, that female imagery, such as birth imagery, suggests that Yahweh has a female aspect', and, second, that such language notwithstanding, Yahweh is indefeasibly male. The argument employs cognitive linguistic theory and suggests that male and female metaphors for Yahweh do not bespeak either maleness or femaleness in the deity, but rather Yahweh's identification with human experience broadly. While the Old Testament emerged in a world dominated by masculine perspectives, it also transforms received concepts, especially in relation to God. This transformative character of the Old Testament can become a model for contemporary readings of the Bible in relation to the contentious area of gender and language for God.